Electron-impact state-to-state cross sections and rate coefficients for X(ν)→B(ν′) excitation of LiH molecule. (15th February 2023) - Celiberto, R; Laricchiuta, A
Abstract: Electron-impact cross sections for the v → v ′ transitions between the vibrational levels of X 1 Σ + and the excited B 1 Π electronic states of LiH molecule, are calculated from threshold to 1000 eV by using the threshold-modified Mott–Massey approximation . Cross sections for the dissociative process, occurring through the excitation to the continuum spectrum of the vibrational levels of the B state, are also obtained. Maxwellian rate coefficients for the corresponding b o u n d − t o − b o u n d and b o u n d − t o − c o n t i n u u m transitions are presented in the temperature range of 0.1–10 000 eV. Finally, scaling relationships for both the v − v ′ cross section and rate coefficients are derived in order to represent the calculated quantities in a compact analytic form.